2018
DOI: 10.1002/sd.1717
|View full text |Cite
|
Sign up to set email alerts
|

Women's needs in new global sustainable development policy agendas

Abstract: This paper provides an audit of how the needs of women are addressed in new global sustainable development policy agendas. The policy agendas audited include the 2030 Agenda for Sustainable Development (AfSD), the Paris Agreement and the Sendai Framework. An auditing matrix of 21 indicators was developed through a critical discourse analysis. Among the indicators identified were: violence against women; capacity building and access to technology; involvement in leadership and decision-making; access to finance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…Several authors have identified the critical importance of aligning the work done in different sectors to achieve the SDGs [39][40][41][42][43][44][45][46][47][48][49]. For example, Rosati and Faria [44] studied how different companies aligned their corporate social responsibility-related activities with the SDGs and found that companies operating in countries with a high level of climate vulnerability are more SDG-aligned.…”
Section: Multistakeholder Partnerships For the Sdgs: Complexities Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have identified the critical importance of aligning the work done in different sectors to achieve the SDGs [39][40][41][42][43][44][45][46][47][48][49]. For example, Rosati and Faria [44] studied how different companies aligned their corporate social responsibility-related activities with the SDGs and found that companies operating in countries with a high level of climate vulnerability are more SDG-aligned.…”
Section: Multistakeholder Partnerships For the Sdgs: Complexities Andmentioning
confidence: 99%
“…SIBs are a hybrid arrangement between social and financial institutions that creates a unique platform to support public-private partnerships between different sectoral actors working collaboratively to achieve the SDGs [45]. Several other studies take a similar sectoral focus making cases for the SDGs in education [42,43,48], in addressing the needs of women [46], for rehabilitating vulnerable communities [47], across value chains [49,50], and in the banking sector [51].…”
Section: Multistakeholder Partnerships For the Sdgs: Complexities Andmentioning
confidence: 99%
“…Nowadays, work‐life balance issues and gender equality are very important for those companies interested in Corporate Social Responsibility and sustainable development (Celma, Martínez‐Garcia, & Coenders, 2014; Nhamo, Muchuru, & Nhamo, 2018; Torres, Jain, & Leka, 2019). Many organizations are aware that an adequate work‐life balance has positive effects on employees' performance and wellbeing (Kobayashi, Eweje, & Tappin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to Sen (2001), the World Bank (2012), and Diiro et al (2016), there is generally a link between employment, health, and well-being of women. Eight out of the 17 SDGs, 1 particularly the fifth and eighth, are centred on females and address women's issues explicitly (Nhamo, Muchuru, & Nhamo, 2018).…”
Section: Introductionmentioning
confidence: 99%